Recent renovation of mechanism and policies for Science and Technology development at local levels and recommendations for future - Luat, Ho Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The renovation process of mechanisms and policies of S&T development including the ones for S&T development at local levels has been conducted on basis of the country’s renovation process. In this process the first lines are for the topics related to the reasoning concepts of the Party to determine the role of S&T and the policies of the State to concretize and realize the guidelines in practice and the impacts of these mechanisms and policies to the local S&T activities. By this way it is possible to identify the impact level of the renovation process of mechanisms and policies of management to S&T activities at local levels and permit us to give proposals and recommendations to push up strongly the S&T activities at local levels in the future time in a more efficient way to meet better its key role for the process of industrialization and modernization of provinces and cities. Code: 11050101